Kyrieleis plaques associated with Herpes Simplex Virus type 1 acute retinal necrosis - Goel, Neha (Saudi J Ophthalmol, 2016)
We report the case of a 55-year-old immunocompetent male who presented with features typical of acute retinal necrosis (ARN). Polymerase chain reaction of the aqueous tap was positive for Herpes Simplex Virus (HSV) – 1. Following therapy with intravenous Acyclovir, followed by oral Acyclovir and steroids, there was marked improvement in the visual acuity and clinical picture. At one week after initiation of treatment, Kyrieleis plaques were observed in the retinal arteries. They became more prominent despite resolution of the vitritis, retinal necrosis and vasculitis and persisted till six weeks of follow-up, when fluorescein angiography was performed. The appearance of this segmental retinal periarteritis also known as Kyrieleis plaques has not been described in ARN due to HSV-1 earlier.